TYPES AND MAIN CHARACTERISTICS OF MONITORING TRAINING OF MODERN ECONOMIC STAFF - K.O. Delyukina (Academy of Cognitive and Natural Sciences, 2008)
This article describes types and main characteristics of monitoring of contemporary economical staff.